Prevalence of Dermatophytic Infections and Their Antifungal Susceptibility Pattern in the Rajshahi Region (TAJ: Journal of Teachers Association, 2023)
Background: Dermatophytes are the most significant fungi because of their widespread involvement in the population and their prevalence worldwide. Bangladesh's hot and humid climate, overcrowded population, poverty, malnutrition, and ignorance make dermatophytosis a common cutaneous infection. These infections occur in both healthy and immunocompromised patients. Dermatophytes are responsible for most cutaneous fungal infections, and the estimated lifetime risk of acquiring a dermatophyte infection is 10-20%.Objective: To isolate and identify different dermatophytes and their antifungal susceptibility pattern in the Rajshahi region.  Materials and Methods: Different clinical samples (e.g., skin scrapings, nail clipping, and hair plucking) were collected under aseptic precautions. The isolation and identification of dermatophytes were performed through a microscopic examination using 10% KOH mount, mycological culture, and species identification by lactophenol cotton blue mount from positive culture. In addition, all dermatophytes isolates were subjected to antifungal susceptibility testing using the agar-based disk diffusion method in Mueller Hinton agar media.Results: Out of 171 samples, Trichophyton rubrum was the predominant dermatophyte species with 76(71.7%), followed by T.mentagrophyte were 15(14.2%), E. floccosum were 12(11.3%), and M. canis were 03(2.8%). voriconazole, clotrimazole, and itraconazole were more effective drugs. Griseofulvin was the least effective drug, followed by fluconazole.Conclusion: This study indicates dermatophytosis is a common skin disease in northern Bangladesh. Due to the increasing trend of antifungal drug resistance among dermatophytes, treatment should be based on antifungal sensitivity testing.TAJ 2022; 36: No-1: 119-125